DESIGN AND DEVELOPMENT OF SIMPLE ACOUSTIC GAS SENSOR FOR MEASURING CONCENTRATION FROM BINARY MIXTURE GAS - BUDIANTO (NIM : 20216037), TOTO
An increasing number of requests for gas sensors appear in many fields on a large scale such as industry and health, as well as on smaller scales such as laboratories and even households. Accurate gas sensors in monitoring gas conditions, cheap, and readily available are the criteria consumers want. One type of gas sensor that can be developed to meet the requirements that consumers want is an acoustic gas sensor. The acoustic gas sensor is a gas sensor that utilizes the characteristics of the sound wave propagation as its detection method. In this research has designed the microcontroller based acoustic gas sensor that can detect and measure gas concentration. This type of gas sensor has the advantage of being able to identify and measure the concentration of many kinds of gas. Also, these types of sensors are easy to develop and cost relatively low. The designed microcontroller-based acoustic gas sensor has been tested to measure the concentration of some gases such as carbon dioxide, oxygen, and hydrogen. The gas to be measured will be mixed with nitrogen gas so that it becomes a binary mixture gas. The results obtained show that the addition of a concentration of the carbon dioxide or oxygen gas will cause a slowing of the velocity of sound waves on the gas mixture medium. Deceleration by carbon dioxide has a higher value than oxygen. Conversely, the addition of a hydrogen gas concentration leads to increase of the propagation of sound. From the five experimental tests of sensors to the three types of gas obtained results consistent with an error value of less than 1% for each gas. One of the main factors to get the measurement result with low error is with temperature control that is keeping the sensor temperature constant at 26Ã‚Â°C during the measurement process. Besides, the gas pressure in the sensor is also held constant at a value of 1 bar. By keeping the temperature and pressure steady, the only variable that can change the speed of the sound wave is the change of concentration of the gas.